Electrocardiographic and Echocardiographic Insights From a Prospective Registry of Asian Elite Athletes - Yeo, Tee Joo; Wang, Mingchang; Grignani, Robert; McKinney, James; Koh, Lay Pheng; Tan, Frankie Hun Yau; Chan, Gregory Chung Tsing; Tay, Nigel; Chan, Siew-Pang; Lee, Chi-Hang; Oxborough, David; Malhotra, Aneil; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Asian representation in sport is increasing, yet there remains a lack of reference values for the Asian athlete’s heart. Consequently, current guidelines for cardiovascular screening recommend using Caucasian athletes’ norms to evaluate Asian athletes. This study aims to outline electrocardiographic and echocardiographic characteristics of the Asian athlete’s heart using a Singaporean prospective registry of Southeast (SE) Asian athletes. Methods and Results 150 elite athletes, mean age of 26.1 ± 5.7 years (50% males, 88% Chinese), were evaluated using a questionnaire, 12-lead electrocardiogram (ECG) and transthoracic echocardiogram. All ECGs were analysed using the International Recommendations (2017). Echocardiographic data were presented by gender and sporting discipline. The prevalence of abnormal ECGs among SE Asian athletes was 6.7% - higher than reported figures for Caucasian athletes. The abnormal ECGs comprized mainly anterior T wave inversions (ATWI) beyond lead V2, predominantly in female athletes from mixed/endurance sport (9.3% prevalence amongst females). None had echocardiographic structural abnormalities. Male athletes had reduced global longitudinal strain compared to females (-18.7 ± 1.6 vs. -20.7 ± 2.1%, p<0.001). Overall, SE Asian athletes had smaller left ventricular cavity sizes and wall thickness compared to non-Asian athletes. Conclusion SE Asian athletes have higher abnormal ECG rates compared to Caucasian athletes, and also demonstrate structural differences that should be accounted for when interpreting their echocardiograms compared to athletes of other ethnicities.